Effects of Mg2+ interstitial ion on the properties of Mg0.5+x/2Si2-xAlx(PO4)3 ceramic electrolytes - Adnan, S.B.R.S.; Halim, Z.A.; Mohamed, N.S. (2017)
Nasicon type, Mg0.5+x/2Si2-xAlx(PO4)3 was synthesized using citric acid assisted sol-gel method. The X-ray diffraction was applied to investigate the effect of extra Mg2+ interstitial ion on the phase, unit cell parameters and structure of the samples. The Mg0.625Si1.75Al0.25(PO4)3 sample exhibited highest bulk conductivity value of 1.54 ×10-4 S cm-1 at ambient temperature. The frequency dependence of the σac of these ceramic electrolytes follows the universal power law variation, σac (ω) = σo + Aωα. The conductivity parameters such as hopping frequencies, charge carrier concentration and mobile ion concentration proved that the increase in conductivity with x was due to the existing of Mg2+ interstitial ion. The experiment results also revealed that the dielectric constant and dielectric loss decreased with frequency. The Mg0.625Si1.75Al0.25(PO4)3 was found to be electrochemically stable up to 2.51 V at ambient temperature.